2017
DOI: 10.20960/nh.1004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and zinc status in amyotrophic lateral sclerosis

Abstract: ResumenIntroducción: hay pruebas considerables de que los cambios en la homeostasis del zinc están relacionados con la patogénesis de la esclerosis lateral amiotrófica (ELA) y que la malnutrición es un factor pronóstico capaz de reducir la supervivencia de los pacientes con ELA. Objetivo: evaluar la ingesta dietética y el estado de zinc en pacientes con ELA, tratados en un centro de atención ambulatoria especializado en Natal, Brasil. Métodos: se incluyeron 20 pacientes con ELA (grupo de casos) y 37 sujetos sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In contrast, TMAO showed no detectable induction for C71G-hPFN1 and nascent hSOD1, even at much higher ratios. Remarkably, we found that the inducing capacity of ATP comes from its triphosphate moiety, which was previously proposed to act as a crucial intermediate in prebiotic chemical evolutions, generating building units for constructing primitive cells and potentially contributing to the Origin of Life 66 , 67 . Furthermore, the inducing capacity of 10 ATP-related molecules was ranked as: ATP = ATPP = PPP > ADP = AMP-PNP = AMP-PCP = PP, while AMP, adenosine, P, and NaCl showed no conversion before aggregation.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, TMAO showed no detectable induction for C71G-hPFN1 and nascent hSOD1, even at much higher ratios. Remarkably, we found that the inducing capacity of ATP comes from its triphosphate moiety, which was previously proposed to act as a crucial intermediate in prebiotic chemical evolutions, generating building units for constructing primitive cells and potentially contributing to the Origin of Life 66 , 67 . Furthermore, the inducing capacity of 10 ATP-related molecules was ranked as: ATP = ATPP = PPP > ADP = AMP-PNP = AMP-PCP = PP, while AMP, adenosine, P, and NaCl showed no conversion before aggregation.…”
Section: Discussionmentioning
confidence: 83%
“…Together, these results demonstrate that caged compound photolysis combined with FSCV can be used to investigate the effects of transient metal ion fluctuations on neurotransmitter dynamics with controlled spatial and temporal resolution. Moreover, dysregulation of zinc homeostasis is associated with the pathogenesis of multiple neurological conditions, including Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, traumatic brain injury, depression, and schizophrenia . Thus, the ability to control the spatial and temporal availability of Zn 2+ ions afforded by our new method could be particularly beneficial in understanding the role of Zn 2+ under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Higher zinc levels in whole blood were also inversely associated with ALS, especially among patients with poor functional capacity [ 13 ]. A Brazilian cross-sectional study found zinc deficiency in ALS patients [ 54 ]. Contradictorily, in a sample of patients with sporadic ALS in China, zinc blood levels did not differ from the control group [ 14 ].…”
Section: Discussionmentioning
confidence: 99%